A half-metallic half-Heusler alloy having the largest atomic-like magnetic moment at optimized lattice constant - Zhang, R. L.; Damewood, L.; Fong, C. Y.; Yang, L. H.; Peng, R. W.; Felser, Claudia (AIP Advances, 2016)
For half-Heusler alloys, the general formula is XYZ, where X can be a transition or alkali metal element, Y is another transition metal element, typically Mn or Cr, and Z is a group IV element or a pnicitide. The atomic arrangements within a unit-cell show three configurations. Before this study, most of the predictions of half-metallic properties of half-Heusler alloys at the lattice constants differing from their optimized lattice constant. Based on the electropositivity of X and electronegativity of Z for half-Heusler alloys, we found that one of the configurations of LiCrS exhibits half-metallic properties at its optimized lattice constant of 5.803Å, and has the maximum atomic-like magnetic moment of 5μB. The challenges of its growth and the effects of the spin-orbit effect in this alloy will be discussed.
CRIS-Team Scopus Importer:2023-03-20